2020
DOI: 10.1109/access.2020.2981492
|View full text |Cite
|
Sign up to set email alerts
|

Combining Spectral and Texture Features for Estimating Leaf Area Index and Biomass of Maize Using Sentinel-1/2, and Landsat-8 Data

Abstract: Leaf area index (LAI) and biomass are important indicators that reflect the growth status of maize. The optical vegetation indices and the synthetic-aperture radar (SAR) backscattering coefficient are commonly used to estimate the LAI and biomass. However, previous studies have suggested that spectral features extracted from a single pixel have a poor ability to describe the canopy structure. In this paper, we propose a method for estimating LAI and biomass by combining spectral and texture features. Specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 57 publications
(71 reference statements)
1
16
2
Order By: Relevance
“…VIs extracted from optic bands are widely used to estimate crop parameters and monitor crop conditions. However, when the crop canopy is dense, optical data tend to be saturated [7]. In addition, since optical data in cloudy conditions are not helpful, SAR sensors use microwave wavelengths that can penetrate clouds and haze [1,[8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…VIs extracted from optic bands are widely used to estimate crop parameters and monitor crop conditions. However, when the crop canopy is dense, optical data tend to be saturated [7]. In addition, since optical data in cloudy conditions are not helpful, SAR sensors use microwave wavelengths that can penetrate clouds and haze [1,[8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Considerable researches have been conducted to estimate various crop parameters using satellite Earth observations, including RADARSAT-2 [1,17,[19][20][21], RapidEye [5,19,20,22,23], Sentinel-1 [7,17,[24][25][26][27][28], Sentinel-2 [7,25,[29][30][31][32], Landsat-5 Thematic Mapper (TM) [33,34], Landsat-7 Enhanced Thematic Mapper Plus (ETM+) [34][35][36], Landsat-8 Operational Land Imager (OLI) [7,17,31,32,[35][36][37], Worldview-2/3 [17,27,28,38,39], and MODIS [40,41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although SRIs are simple to calculate and several indices have been effective in estimating measured traits, they are constrained by their use of just a few bands and are affected by vegetation saturation or varying degrees, as well as timeliness and regional specificity [ 38 , 39 , 40 , 41 , 78 , 79 ]. Multivariate regression models such as PLSR and MIR have previously been shown to be alternative methods to SRIs for explaining the relationships between plant-measured traits and spectral reflectance and perform equally well or better than SRIs for estimating the changes in these traits [ 42 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Han et al [ 78 ] found that MLR based on remote-sensing spectral data produced acceptable accuracy in predicting above-ground biomass. In addition, Luo et al [ 79 ] found that both the MLR and support vector machine (SVR) models based on spectral data showed the accuracy estimation of LAI and biomass of maize at the flowering stage since the growth and development of a maize canopy reaches a plateau at flowering, and LAI and biomass no longer grow as quickly. The overall results indicate that the proposed PLSR and MLR models based on the combination of vegetation-SRIs from two methods can improve the accuracy of plant trait estimates.…”
Section: Resultsmentioning
confidence: 99%